2017
DOI: 10.1002/dev.21497
|View full text |Cite
|
Sign up to set email alerts
|

Mild perinatal adversities moderate the association between maternal harsh parenting and hair cortisol: Evidence for differential susceptibility

Abstract: It has been shown that following exposure to mild perinatal adversity, children have greater susceptibility to both the negative and positive aspects of their subsequent environment. In a large population-based cohort study (N = 1,776), we investigated whether mild perinatal adversity moderated the association between maternal harsh parenting and children's hair cortisol levels, a biomarker of chronic stress. Mild perinatal adversity was defined as late preterm birth (gestational age at birth of 34-37 weeks, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 86 publications
(131 reference statements)
2
19
0
Order By: Relevance
“…In 11 studies that examined between one and four indicators of adversity, four reported no associations with hair cortisol (Boeckel et al, 2017;Flom, et al, 2017;Gerber et al, 2017;Olstad et al, 2016), five reported associations with one indicator (Ouellette et al, 2015;Palmer et al, 2013;Ursache et al, 2017;Vaghri et al, 2013;Vliegenthart et al, 2016), and two studies reported associations with two indicators (Rippe et al, 2016;Windhorst et al, 2017). Where associations are reported, often they are not replicated by other studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 11 studies that examined between one and four indicators of adversity, four reported no associations with hair cortisol (Boeckel et al, 2017;Flom, et al, 2017;Gerber et al, 2017;Olstad et al, 2016), five reported associations with one indicator (Ouellette et al, 2015;Palmer et al, 2013;Ursache et al, 2017;Vaghri et al, 2013;Vliegenthart et al, 2016), and two studies reported associations with two indicators (Rippe et al, 2016;Windhorst et al, 2017). Where associations are reported, often they are not replicated by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings draw on studies which have primarily used cohorts unselected for experience of adversity (Karlén et al, 2015;Rippe et al, 2016;Windhorst et al, 2017). These findings draw on studies which have primarily used cohorts unselected for experience of adversity (Karlén et al, 2015;Rippe et al, 2016;Windhorst et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations